Features of Disfluent speech by EFL Learners at Taiz University - Abeer Al-Ghazali (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
This paper aims at investigating the features of disfluent speech by EFL learners at Taiz University. Disfluent speech features usually lead to listeners’ negative impressions on the EFL learners’ speech. This paper focuses on repair fluency aspects as fillers, repetitions, restarts and reformulations. Analysing those features contributes to the understanding of the ongoing learner’s needs that should be put into concentration during teaching. The data was collected from 20 level four students of English Language major, Faculty of Education, Taiz University. The participants were asked to narrate the events of a short silent video. The quantitative analysis showed that the participants overused disfluencies such as fillers, prolongations, repetitions, restarts and self-corrections. The mostly present self corrected item was the pronouns. This paper recommends that in order for the EFL learners to make their speech sound more fluent and more natural, they should be firstly introduced to the notion of disfluent speech features, and then they should be trained using some activities that focus on fostering fluency.